Association between endocrine disrupting chemicals exposure and the risk of all-cause mortality in individuals with diabetes mellitus or its complications: A prospective cohort study - Yueheng Zhang; Zilong Zhang; Feiyang Zhou; Guangchao Xu; Weichao Huang; Maoyang Wang; Yuanqi Lan; Wei Zhang; Zhiyuan Liu; Shusen Chang; Shi Qiu; Fang Qi; et al. (Environment International)
Objective: To investigate the association between exposure to endocrine disrupting chemicals (EDCs) and all-cause mortality in individuals with diabetes mellitus (DM) in U.S., including those with diabetic complications. Methods: This prospective cohort study included participants with DM in the 1999–2018 National Health and Nutritional Examination Survey. Data on mortality was obtained from national death records up to December 31, 2019. Cox regression, WQS regression and LASSO regression were constructed to examine the associations between EDCs and all-cause mortality in individuals with DM or its complications, adjusted for potential confounders. Restricted cubic spline analysis was used to investigate the linear relationship. Subgroup analyses were also tested in prespecified subgroups of interest. Results: The study included 3,453 participants. Mono-(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), mono-(2-ethyl-5-oxohexyl) phthalate (MEOHP), and mono-2-ethyl-5-carboxypentyl phthalate (MECPP) showed positive associations with all-cause mortality (MEHHP: 1.14 (CI1.00–1.29); MEOHP: 1.14 (CI 1.00–1.30); MECPP: 1.17 (CI 1.00–1.37)). These also exhibited positive associations with all-cause mortality in the participants with diabetic kidney disease (MEHHP: 1.24 (CI 1.08–1.42); MEOHP: 1.27 (CI 1.10–1.47); MECPP: 1.43 (CI 1.19–1.71)). Bisphenol A 1.45 (1.08, 1.96) and MCPP 1.59 (CI 1.24–2.05) showed positive associations with all-cause mortality in the diabetic retinopathy (DR) participants. MEHHP exposure interacted with hypertension in DM and hypercholesterolemia, as well as with age in DR populations. MCPP exposure interacted with age in DR, significantly amplifying mortality risks (P interaction < 0.05). Conclusions: This study provided epidemiological evidence that higher concentrations of certain EDCs are associated with an increased risk of all-cause mortality in participants with DM or its complications.